A randomized, multi-center, open-label study to compare the safety and efficacy between afatinib monotherapy and combination therapy of afatinib and HAD-B1 for the locally advanced or metastatic NSCLC patients with EGFR mutations. Issue 49 (4th December 2020) - Song, Si-Yeon; Ha, Su-Jeong; Park, Ji-Hye; Park, So-Jung; Shin, Seong Hoon; Oak, Chulho; Choi, Jun-Yong; Yoon, Seong Woo; Kim, Jung-A; Yoon, Seong Hoon; Son, Ji Woong; Kim, Seung Joon; et al.
Abstract: Background: Afatinib is an epidermal growth factor receptor - tyrosine kinase inhibitor (EGFR-TKI) with proven efficacy for treating patients with advanced or metastatic non-small cell lung cancer (NSCLC). Unfortunately, responses are limited by acquired resistance. Because traditional Korean medicine may have synergistic effects when combined with chemotherapy or radiotherapy, the aim of our study is to elucidate the efficacy and safety of afatinib plus HangAmDan-B1 (HAD-B1) combination therapy in the treatment of patients with NSCLC, as well as EGFR mutations, who need afatinib therapy. Methods/design: This study is a randomized, multi-center, open clinical trial. A total of 178 eligible subjects, recruited at 8 centers, are randomly assigned to take Afatinib (20–40 mg) ± HAD-B1 (0.972 g/day) for 48 weeks. In the test group, HAD-B1 and afatinib will be used in combination. The primary outcome is a comparison of progression-free survival (PFS) between afatinib monotherapy and afatinib plus HAD-B1 combination therapy in patients with local advanced or metastatic (Stage IIIA, B, C/IV) NSCLC. Secondary outcomes are the overall survival rates, clinical responses, tumor size reductions, health-related qualities of life, and safety. Discussion: The result of this clinical trial will provide evidence for the efficacy and safety of using HAD-B1 in the treatment of EGFR-positive patients with locally advanced or metastatic NSCLC who require afatinib therapy. Trial registration: Clinical Research Information Service (CRIS), Republic of Korea (ID: KCT0005414), on September 23, 2020.